Evaluation of User Interface and User Experience on Solo Destination App using System Usability Scale and Human-centered Design Methods - Muhammad Wildan Yasykur; Devi Ajeng Efrilianda (Universitas Negeri Semarang, 2024)
User interface (UI) and user experience (UX) play a crucial role in determining a system's usability. Although designed for widespread use, the Solo Destination app has not been assessed for its usability. This study evaluates the app using the System Usability Scale (SUS) and Human-Centered Design (HCD) methods. The sample size was determined using Slovin’s formula, resulting in 50 participants, with 5 chosen for in-depth interviews to gain deeper insights. The initial evaluation showed that the app scored 55.55 on the SUS, placing it in the marginal low category within the acceptability range. This score corresponds to a grade scale of D and an